IMPLEMENTASI PROTOKOL PALERMO DALAM MENANGGULANGI PERMASALAHAN TENAGA KERJA WANITA INDONESIA YANG MENJADI KORBAN HUMAN TRAFFICKING - Moeri, Marcellena Nirmala Chrisna; Fasisaka, Idin; Kawitri Resen, Putu Titah (Program Studi Hubungan Internasional FISIP Universitas Udayana, 2016)
ABSTRACT This research describes an implementation of the Palermo Protocol as an international law in Indonesia in an affort to overcome the problems of Indonesian’s Woman Labour who are victims of human trafficking throught the point of view of human security. Indonesia not only as a sending country, but also a transit and destination country for the human trafficking issue. This study will elaborate on three things: first, there has been setup in an effort to combat and prevent human trafficking throught the international instruments called the Palermo Protocol in 2000. Second, in Indonesia human trafficking has occurred since the royal era in Indonesia. However, Indonesia does not have a law that can be used to view the exact definition related to human trafficking, the punishment that is fitting to the perpetrators, and to provide protection for victims of human trafficking so that problem can not be solved properly. Third, Indonesia have ratified the Palermo Protocol, this is expected to be a solution to law enforcement for victims of human trafficking in Indonesia Key Words: Indonesian’s Woman Labour, the Protokol Palermo, Human Security, Human Trafficking